Design and implementation of line follower and obstacle detection robot - Ahmed Bendimrad; Ayoub El Amrani; Bouchta El Amrani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this paper, we propose a method for a line follower robot based on the instantaneous computation of the radius of curvature of this line, using infrared line sensors. The number and layout of its sensors, as well as the method chosen, play an important role in the robot's response to the line, with the desired accuracy and speed. In addition, the robot must be equipped with an anti-collision system, using an ultrasonic distance sensor, to detect and avoid obstacles in several situations, especially at line crossovers, when other robots share a common complex line.